A structured light laser probe for gastrointestinal polyp size measurement: a preliminary comparative study - Visentini-Scarzanella, Marco; Kawasaki, Hiroshi; Furukawa, Ryo; Bonino, Marco Augusto; Arolfo, Simone; Lo Secco, Giacomo; Arezzo, Alberto; Menciassi, Arianna; Dario, Paolo; Ciuti, Gastone (Endoscopy International Open, 2018)
Background and study aims Polyp size measurement is an important diagnostic step during gastrointestinal endoscopy, and is mainly performed by visual inspection. However, lack of depth perception and objective reference points are acknowledged factors contributing to measurement errors in polyp size. In this paper, we describe the proof-of-concept of a polyp measurement device based on structured light technology for future endoscopes.Patients and methods Measurement accuracy, time, user confidence, and satisfaction were evaluated for polyp size assessment by (a) visual inspection, (b) open biopsy forceps of known size, (c) ruled snare, and (d) structured light probe, for a total of 392 independent polyp measurements in ex vivo porcine stomachs.Results Visual assessment resulted in a median estimation error of 2.2 mm, IQR = 2.6 mm. The proposed probe can reduce the error to 1.5 mm, IQR = 1.67 mm (P = 0.002, 95 %CI) and its performance was found to be statistically similar to using forceps for reference (P = 0.81, 95 %CI) or ruled snare (P = 0.99, 95 %CI), while not occluding the tool channel. Timing performance with the probe was measured to be on average 54.75 seconds per polyp. This was significantly slower than visual assessment (20.7 seconds per polyp, P = 0.005, 95 %CI) but not significantly different from using a snare (68.5 seconds per polyp, P = 0.73, 95 %CI). However, the probe’s timing performance was partly due to lens cleaning problems in our preliminary design. Reported average satisfaction on a 0 – 10 range was highest for the proposed probe (7.92), visual assessment (7.01), and reference forceps (7.82), while significantly lower for snare users with a score of 4.42 (P = 0.035, 95 %CI).Conclusions The common practice of visual assessment of polyp size was found to be significantly less accurate than tool-based assessment, but easy to carry out. The proposed technology offers an accuracy on par with using a reference tool or ruled snare with the same satisfaction levels of visual assessment and without occluding the tool channel. Further study will improve the design to reduce the operating time by integrating the probe within the scope tip.